How Fathers' Involvement Shapes Children's Social-Emotional Wellbeing in Adulthood - Mashudi, Esya Anesty; Nazilah, Mahdatu Bayatina (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2024)
Social-emotional development is crucial for children's well-being. Parental support, especially from fathers, can significantly contribute to positive experiences and healthy growth. This study explores the impact of a father's absence on a child's development. Through qualitative interviews with two individuals, 'B' and 'N,' who lacked paternal involvement in childhood, we found that the absence of a father can lead to significant social-emotional challenges. These include difficulty managing emotions, unresolved trauma, low self-confidence, and difficulties in social interactions. This research highlights the importance of a father's presence in a child's life for healthy development.